Dyadic Death Two Case Report - Odabaşı, Aysun Balseven; Demirel, Birol; Akar, Taner; Dinç, Ahmet Hakan; Ünal, Bahri Melih (The Bulletin of Legal Medicine, 2005)
The suicide of a person after committing homicide, and/or two people committing suicide together is termed as dyadic death. Such events are usually domestic, occur by the use of fire-arms-with the murderer being male, the victim female-and encountered rarely in Turkey and around the world as well. Two cases of dyadic deaths that took place in Ankara between 1999 and 2003 are presented. One of them is committed with a firearm and the other with an incisive-perforating instrument and both ending with suicide by hanging. The cases are discussed with reference to other cases previously reported in Turkey and the literature. Key words: Dyadic death, hanging, homicide-suicide